Penerapan Algoritma Apriori Pada Analisa Data Penjualan Ecommerce - Muliati Badaruddin; Rayendra Rayendra (STMIK Budi Darma, 2022)
Already all sectors are now using the role of this technology. The role of technology in the business sector is to carry out online transactions that can be done anytime and anywhere or commonly referred to as E-commerce. Now E-commerce has grown very rapidly, this is because there are many benefits that can be obtained from the use of E-commerce. But that does not mean that the use of e-commerce is not experiencing losses, the use of e-commerce that is not on target will also create losses for business people. Of course this is a problem that must be solved wisely by being able to read the pattern of goods requested by consumers or products that are not in demand by consumers. Where to find out the pattern can be seen from the e-commerce sales data that is already available. Data mining is a technique used to perform data processing. Data processing is carried out in data mining to obtain new information that can be implemented. A priori algorithm is a method used to find a pattern of relationships between one or more dataset items. In the results of the study, it was found that there are 3 items of E-commerce sales data that can be prioritized for sales. Where of the three items there are 3 combinations of items A1èA2 with a support value of 40% and a confidence value of 67%. A combination of items A1èA5 with a support value of 50% and a confidence value of 83%. Combination of items A2èA5 with a minimum support value of 40% and a confidence value of 50%